Answer:
5
Step-by-step explanation:
D² = ( x2 - x1 )² + ( y2 - y1 )²
= [ (-18) - (-18) ]² + [ (-1) - (-6) ]²
= ( -1 + 6 )²
D² = ( 5 )²
hence, D = 5
Answer:
No
Step-by-step explanation:
y^2 = x^2 + 5
Rewriting
y^2 - x^2 = 5
This is a hyperbola
We can use the vertical line test to show that it is not a function since a vertical line passes through more than one point.
Answer:
<u>y = -1 (x) -1</u>
Step-by-step explanation:
If you plug in the numbers from the coordinates into the equation, you will find that it's true.
-1 is x and 0 is y. Plug in the #s like so:
y = -1 (x) -1
0 = -1 (-1) - 1
0 = 1 - 1
0 = 0
Therefore, the equation above represents the line that passes through both these points.
Answer:
264 with a remainder of 4
Step-by-step explanation:
Answer:
625 cm^2
Step-by-step explanation:
Break it into a rectangle on the bottom and a triangle on top
rectangle area = 50 x 8 = 400 cm^2
triangle area = 1/2 b * h = 1/2 * 50 * 9 = 225 cm^2
added together = 625 cm^2